Developing an integrated framework for supplier evaluation based on relevant attributes and performance measures - Cheshmberah, Mohsen (Logistics and sustainable transport, 2020)
Supplier evaluation and selection is essential to any organization, and planning an effective and comprehensive approach to that end seems inevitable. Meanwhile, determining the requisite criteria for evaluating and selecting suppliers is probably one of the most important steps to be taken towards developing an evaluation and selection model in the organization. In this article, first a review of the literature on the criteria and the field of supplier evaluation and selection are provided. These criteria are then placed into proper categories. In order to formulate a supplier evaluation and selection framework for the manufacturing organization under study, the implemented categorization is applied where a list of fifteen attributes and performance criteria is created; where upon it is secured with the help of a designated panel (project team). These features are then screened using Lawshe's method the "social attribute" is removed from the list of fifteen. The remaining 14 other criteria are configured within the SEAP (Suppliers Evaluation based on Attributes and Performances) framework. The framework follows the objective of continually evaluating suppliers, both potential and actual ones through incorporating their performances into their qualification ratings. Based on the proposed framework, suppliers are evaluated on the basis of two types of criteria, - feature (attribute) and performance.
Keywords: atributi; attributes; criteria; evalvacija dobavitelja; framework; izbor dobaviteljev; kriteriji; Lawshejeva metoda; Lawshe's method; merjenje uspešnosti; okvir; performance measurement; supplier evaluation; supplier selection